Qualidade de vida e complicações decorrentes da colostomia úmida em dupla-boca como opção de desvios urinário e fecal simultâneos - Luciana Maria Pyramo Costa (2007)
The double-barrelled wet colostomy was described by Carter et al in 1989 and constitutes an option for patients who need a simultaneous urinary and faecal diversion. The advantages of this procedure are absence of entero-enteric anastomosis and simultaneous faecal and urinary diversion, using a single stoma. Up to the present moment, a few studies with short series have been published. The objectives of this study were to identify the early and late complications comparing them to literature, to evaluate the influence of the residual volume of the urinary conduit in the metabolic and renal disturbances, to identify macroscopic changes in the mucosa of the urinary reservoir and stoma and toevaluate the quality of life of the patients with double-barrelled wet colostomy in comparison to the control group. Nineteen patients who undertook the operations in the hospitals Governador Israel Pinheiro and Felício Rocho in Belo Horizonte, Minas Gerais, from February 2001 to January 2007, by the revision of medical records and evaluation of living patients (n = 12). The quality of life had been evaluated using the questionnaires Medical Outcomes Study 36 Item Short Form Health Survey (SF-36) and European Organization of Research and Treatment of Cancer Quality of Life Questionnaire (QLQ-C30). The operative mortality and the morbidity rates directly related to double-barrelled wet colostomywere 0% and 36.8%, respectively. The fistula was the most frequent complication (15.7%), with necessity of surgical treatment in two patients. Anastomotic stenosis (5.2%), hydronephrosis (5.2%) and pyelonephritis (5.2%) were complications treated clinically. Hyperchloremic metabolic acidosis was found in one patient with 60 mL of residual volume in the urinary reservoir. There wasn't any patient who presented complications related to the stoma and there was no macroscopic alteration in the mucosa of the urinary reservoir. According to the questionnaire QLQ-C30 and SF-36, the patients presented good quality of life. It can be concluded that the early and late complications are compatible with the literaturedata. The small residual urinary volume avoids metabolic and renal disturbances. There were no macroscopic charges in the urinary reservoir and stoma in the first years and the patients quality of life alterates little in comparison to the control group.